SEABIRDS IN THE BANDA SEA IN FEBRUARY/MARCH 1985 - Cadee, G. C. (Marine Research in Indonesia, 1989)
Quantitative seabird data were collected in February/March 1985 in the Banda Sea. Comparison with similar data for August 1984 indicated no monsoonal influence on seabrid abundance; the median for both periods falls within the 1-5 birds per hour class.The area around the breeding island Manuk was relatively rich in both periods. Birds breeding here are "blue ocean" seabirds, foraging over large areas. Apparently, not food abundance but suitable breeding place determines their abundance here. Manuk has an enormous importance for the seabird population in the Banda Sea area, fortunately, it is a nature reserve since 1981. The breeding period on Manuk is not short and related to the NE monsoon, but extended over a larger period of the year. Manuk was known already as a breeding island in the 17th cnetury, but this knowledge was lost and only recently Manuk was "rediscovered" as such.A second relatively rich area occurred again south of Irian Jaya. Migrating birds dominated here. They probably visit this area because of relatively high food availability. Species differed for both periods. Streaked Shearwaters which breed on the northern hemisphere had in February/ March replaced the antarctic Wilson's Stormpetrel which abounded here in August 1984, but had now returned to its breeding area.